Development of Smartphone-Based Physics Experimental Module (EFISMART) - Asep Irvan Irvani; Resti Warliani; Siti Nurdianti Muhajir; Rahmadhani Mulvia (Journal of Natural Science and Integration, 2025)
This study presents the development of EFISMART, a smartphone-based physics experiment module designed toenhance students’ conceptual understanding through interactive and hands-on learning experiences. The primary aimis to develop an innovative and effective educational tool that integrates modern technology into physics learning topromote deeper engagement and comprehension. Employing a mixed-methods approach with an explanatory design,this research combines quantitative and qualitative data to assess both validity and effectiveness. The module underwentexpert validation involving three specialists in physics, pedagogy, and language. The resulting average scores—4.32(86.4%), 4.15 (83.0%), and 4.60 (92.0%)—indicate a “Very Valid” classification across all domains. Thesefindings confirm that EFISMART meets scientific, pedagogical, and linguistic standards of quality. A limited trialinvolving 16 students demonstrated that the module effectively enhanced learner engagement, conceptual mastery, andexperimental skills. Overall, EFISMART offers a contextual and technology-enhanced approach to physicseducation, promoting practical competence and a more meaningful understanding of scientific concepts. The module istherefore recommended for broader implementation in educational settings to support active and inquiry-based learningin scienceKeywords: EFISMART, phyphox, hands-on experiments, physics education, smartphone-based learning